A clue to the diagnosis of TAPVD. (15th May 2012) - Jones, Andrew J; Zieba, Krzysztof; Starling, Luke; Longman, Joanna
Abstract : Total anomalous pulmonary venous drainage (TAPVD) is a rare form of congenital heart disease where all four pulmonary veins drain to the systemic venous circulation. A term infant was found to have low oxygen saturations on the neonatal check and he was admitted to the neonatal intensive care unit. An increasing oxygen requirement necessitated invasive ventilation. A blood gas taken from the umbilical venous catheter (UVC) showed a pO2 of 28.1kPa – a finding that at the time was considered to be erroneous. An x-ray showed the UVC tip was located in the liver. The following day the baby was transferred to a cardiology centre where a diagnosis of unobstructed infracardiac TAPVD was made on echocardiography. In retrospect the unusually oxygenated venous gas was consistent with pulmonary venous return draining directly to the hepatic venous system. This could have provided a vital clue to diagnosis in a situation where an echocardiogram was not available.